2020
DOI: 10.3892/etm.2020.9258
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA‑MALAT1 expression in patients with coronary atherosclerosis and its predictive value for in‑stent restenosis

Abstract: This study was designed to investigate the long non-coding RNA (lncRNA)-metastasis associated lung adenocarcinoma transcript 1 (MALAT1) expression in patients with coronary atherosclerosis and its predictive value for in-stent restenosis. Ninety-five patients with coronary heart disease who came to our hospital for treatment and underwent stent implantation were selected as a research group (RG), and 95 volunteers undergoing physical examination who did not suffer from coronary heart disease during the same pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
(20 reference statements)
0
11
2
Order By: Relevance
“…According to previous evidence that demonstrated Malat1 and THRIL expressions were upregulated in atherosclerotic patients with coronary artery diseases [18,19,21,28] we hypothesized that in patients with atherosclerotic IS Malat1 and THRIL expression may be upregulated although present results supported our hypothesis this is in contradiction with Ren's study, This controversy could be attributed to the types of stroke and/or time of blood sampling. We had 59 IS cases with LAA and SVD while in Ren's study the Malat1 level was assessed in 120 IS patients with all types of stroke.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…According to previous evidence that demonstrated Malat1 and THRIL expressions were upregulated in atherosclerotic patients with coronary artery diseases [18,19,21,28] we hypothesized that in patients with atherosclerotic IS Malat1 and THRIL expression may be upregulated although present results supported our hypothesis this is in contradiction with Ren's study, This controversy could be attributed to the types of stroke and/or time of blood sampling. We had 59 IS cases with LAA and SVD while in Ren's study the Malat1 level was assessed in 120 IS patients with all types of stroke.…”
Section: Discussioncontrasting
confidence: 93%
“…Malat1 accelerates the accumulation of cholesterol-lled foam cells in blood vessels and enhances lipid uptake in macrophages by CD36 expression and subsequently promotes the atherosclerosis process [20]. Recent studies have identi ed the overexpression of Malat1 in patients with CAD while has shown its predictive value for in-stent restenosis, positive correlation with in ammatory factors, and regulation of coronary slow ow endothelial dysfunction [18,19,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was significantly upregulated in the blood of CAD patients of different clinical phenotypes and associated with disease severity [ 13 , 46 , 47 , 48 ]. Moreover, recent research has indicated that MALAT1 could not only be a helpful diagnostic cardiac biomarker but also valuable for the prediction of in-stent restenosis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, serum lncRNA-AWPPH is an independent risk factor for coronary artery disease and lncRNA THRIL is positively related to the accumulating rate of major adverse cardiovascular events in patients with coronary heart disease [ 14 , 15 ]. An analysis manifests that the expression of lncRNA MALAT1 is elevated in humans with coronary atherosclerosis and has prognostic significance for in-stent restenosis [ 16 ]. LncRNA Sox2 overlapping transcript (SOX2-OT) is an lncRNA located in human chromosome 3q26.33 locus.…”
Section: Introductionmentioning
confidence: 99%